2015
DOI: 10.1017/s0950268815000655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thyroid hormone disruption on the incidence of shingles

Abstract: SUMMARY The reactivation of dormant alpha-Human Herpes Virus (αHHV) has been attributed to various causes often referred to as stressors. However, no clinical study investigating the relationship between stressors and reactivation exists in humans at this time. Herpes Simplex Virus Type-1 (HSV-1), an important αHHV, was shown to have its gene expression and replication regulated by Thyroid hormone (TH) using molecular biology approaches. Varicella Zoster Virus (VZV) is categorized in αHHV superfamily and share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
(13 reference statements)
2
15
0
Order By: Relevance
“…Common risk factors that may increase the chance of causing shingles are shown as being older than 50, having a weakened immune system due to diabetes or HIV infection, suffering stress or trauma, or undergoing cancer treatment, etc. 37 The relationship of thyroid hormone disruption and the pathophysiology of shingles were mentioned but not well-studied 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Common risk factors that may increase the chance of causing shingles are shown as being older than 50, having a weakened immune system due to diabetes or HIV infection, suffering stress or trauma, or undergoing cancer treatment, etc. 37 The relationship of thyroid hormone disruption and the pathophysiology of shingles were mentioned but not well-studied 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis our lab has studied the effect of thyroid hormone treatments on HSV-1 infections using different models. In addition, our lab has reported results from two retrospective clinical data analyses where patients with thyroid hormone complications increased the odds ratio of having herpes virus reactivation [3, 4]. The first study identified that several specific age/gender hospitalized patient groups at a comprehensive research medical center in urban Taiwan, with thyroid disorders were 2 times more likely to also have a αHHV [4].…”
Section: Introductionmentioning
confidence: 99%
“…The first study identified that several specific age/gender hospitalized patient groups at a comprehensive research medical center in urban Taiwan, with thyroid disorders were 2 times more likely to also have a αHHV [4]. The second study identified that hospitalized patients at a regional hospital in rural Maryland with thyroid disorders were 3 times more likely to have VZV diagnoses [3]. To understand these clinical observations, our lab studies cellular thyroid hormone action in regards to transcriptional regulation and signal transduction and have found that both mechanisms might be affecting HSV-1 infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormonal (T 3 ) fluctuation was recently proposed to play a role in regulating HSV-1 replication in neurons [26-29]. It exerts its physiological and biological functions primarily through its nuclear receptor thyroid hormone receptor (TR) [30].…”
Section: Introductionmentioning
confidence: 99%